On the Relative Catch Efficiency of Different Shaped Otter Boards in Bottom Trawling - NARAYANAPPA, G. (Fishery Technology, 1968)
Three different types of otter boards varying in shape weretried to find out their relative catch efficiency. They were operatedwith two types of nets. The results indicated that the curved otterboards gave more catch per unit effort with all the combinations ofnets and riggings tried.